CONSTRUCTION OF B-FOCAL CURVES OF SPACELIKE BIHARMONIC B-SLANT HELICES ACCORDING TO BISHOP FRAME IN E(1, 1) - Korpinar, Talat; Turhan, Essin (Accad Peloritana Pericolanti, 2012)
In this paper we find parametric equations of B-focal curves of spacelike biharmonic B-slant helices according to Bishop frame in terms of Bishop curvatures in the Lorentzian group of rigid motions E(1, 1).
Keywords: Time-Like